Monoclonal antibodies specific for elongation factor Tu and complete nucleotide sequence of the tuf gene in Mycobacterium tuberculosis. - Carlin, N I (1992)
Monoclonal antibodies against mycobacterial antigens were produced by immunizing LOU/C rats with live Mycobacterium bovis BCG. The antibodies were characterized by an enzyme-linked immunosorbent assay and by sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by Western blotting (immunoblotting). One antibody, MAMB 2, reactive with a 47-kDa protein was used to screen a lambda gt11 M. tuberculosis gene library (R. A. Young, B. R. Bloom, C. M. Grosskinsky, J. Ivanji, D. Thomas, and R. W. Davis, Proc. Natl. Acad. Sci. USA 82:2583-2587, 1985). Three recombinant phages reactive with MAMB 2 in plaque lysates were isolated, and part of the insert was sequenced. The mycobacterial inserts were all expressed as proteins fused with beta-galactosidase when the phages were induced as lysogens in Escherichia coli. The entire M. tuberculosis tuf gene was obtained by screening the lambda gt11 library with a DNA probe specific for the primary clones. A phage isolated from this screening was able to express the native protein in E. coli when introduced as a lysogen. A comparison of the entire gene sequence and the deduced protein sequence with the EMBL DNA and Swiss-Prot protein data libraries revealed strong homologies with elongation factors of bacteria, yeast mitochondria, and a plant chloroplast.